Repesentasi Tuturan Campur Kode Mahasiswa IAIN Ambon dalam Pembelajaran Bahasa Indonesia di Era Merdeka Belajar: IAIN Ambon Student Code Mix Speech Representation in Indonesian Language Learning in the Free Learning Era - Handayani, Nanik; Mirna, Wa; Syaidah, Syaidah; Rambe, Nana Ronawan (Balai Bahasa Provinsi Papua, 2024)
This study describes how code mixing and the causes of code mixing in lecture activities at the Islamic Broadcasting Communication Study Program (KPI), Islamic Counseling Guidance Study Program (BKI) & Islamic Philosophy Akidah (AFI) at IAIN Ambon. The research uses descriptive techniques. The research data used is the language between students in the Indonesian language learning process. The research data is in the form of speech between students during the Indonesian language learning process in the classroom which contains elements of code mixing. The research data collection step begins with identifying, classifying, analyzing and concluding the findings. The results of this study indicate that the form of code mixing is in the form of words, phrases, and sentences while the triggers of code mixing in the learning process aim to provide information, explain, confirm, and to know while the factors that influence code mixing, namely the environment, everyday language , peers and topics of conversation.